2016
DOI: 10.3168/jds.2015-10676
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for hock and knee injuries on dairy cows in tiestall housing in Canada

Abstract: Leg injuries on dairy cows are a common and highly visible welfare concern on commercial dairy farms. With greater attention being placed on food animal welfare and limited research being conducted on tiestall farms, this study aimed to identify prevalence and risk factors for hock and knee injuries on dairy cows housed in tiestall barns in Ontario (n=40) and Quebec (n=60). A sample of 40 cows was purposively selected per farm and several animal- and farm-based measures were taken. Both hocks and both knees on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
68
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(88 citation statements)
references
References 30 publications
14
68
6
Order By: Relevance
“…Moreover, only farmers practicing the traditional seasonal movement of the entire herd from valley farms to highland pastures during summer were included. Tie-stall systems were predominant (almost 70%) in the sample, as expected for small-scale systems in general and mountain farming systems during winter specifically (Sturaro et al, 2013;Nash et al, 2016).…”
Section: Study Area and Farmssupporting
confidence: 61%
“…Moreover, only farmers practicing the traditional seasonal movement of the entire herd from valley farms to highland pastures during summer were included. Tie-stall systems were predominant (almost 70%) in the sample, as expected for small-scale systems in general and mountain farming systems during winter specifically (Sturaro et al, 2013;Nash et al, 2016).…”
Section: Study Area and Farmssupporting
confidence: 61%
“…Another measurement collected was the height of the cow at the rump and the width at the hook bones, as described by Nash et al (2016). In tiestalls, this measurement was collected on all of the animals entered into the study and used to determine whether the dimensions of their stalls were appropriate for their size.…”
Section: On-farm Assessmentmentioning
confidence: 99%
“…Two Canadian studies found a prevalence of neck lesions of 4% in tiestall facilities (Zurbrigg et al, 2005a) and 9% in freestall facilities (Zaffino Heyerhoff et al, 2014). The overall prevalence of hock and knee lesions reported in these studies was quite high; however, within individual herds the prevalence of these lesions can be very low to none (von Keyserlingk et al, 2012;Zaffino Heyerhoff et al, 2014;Nash et al, 2016), demonstrating that reducing lesions is an achievable goal for producers.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations